Analysis of implementation of Tradable Green Certificates system in a competitive electricity market: A game theory approach - Meysam Ghaffari; Ashkan Hafezalkotob; Ahmad Makui (Journal of Industrial Engineering International, 2016)
This paper investigates three models to implement Tradable Green Certificates (TGC) system with aid of game theory approach. In particular, the competition between thermal and renewable power plants is formulated in three models: namely cooperative, Nash and Stackelberg game models. The price of TGC is assumed to be determined by the legislative body (government) which is fixed. Numerical examples presented in this paper include sensitivity analysis of some key parameters and comparison of the results of different models. In all three game models, the parameters that influence pricing of the TGC based on the optimal amounts are obtained. The numerical examples demonstrate that in all models: there is a reverse relation between the price of electricity and the TGC price, as well as a direct relation between the price of electricity and the share of green electricity in total electricity generation. It is found that Stackelberg model is an appropriate structure to implement the TGC system. In this model, the supply of electricity and the production of green electricity are at the highest level, while the price of electricity is at the lowest levels. In addition, payoff of the thermal power plant is at the highest levels in the Nash model. Hence this model can be an applicatory structure for implementation of the TGC system in developing countries, where the number of thermal power plants is significantly greater than the number of renewable power plants.
Keywords: 650; Green electricity; Tradable Green Certificate; Game theory; Renewable energy